"Helping teenagers in care flourish: What parenting research tells us about foster care". Issue 3 (30th July 2019) - Coleman, John
Abstract: In this article, I review a range of theoretical and practical issues that are relevant to the foster care of teenagers. I argue that topics such as the recent research evidence from neuroscience regarding brain development in adolescence, as well as control, the promotion of autonomy, and resilience, all have major implications for the provision of appropriate care for teenagers. I outline some of the key conclusions reached by researchers on these pertinent topics and then go on to consider the implications from this evidence for the training of foster carers.